The effectiveness of resource-saving methods of tillage of dark gray forest soil in the crop rotation link - D. A. Dementyev; I. Yu. Ivanova; A. A. Fadeev (Аграрная наука Евро-Северо-Востока)
The article examines the impact of various aggregates for primary autumn tillage of dark gray forest soil on its agrophysical parameters, productivity and economic efficiency of the crop rotation link. The experiment was carried out in the conditions of the Chuvash Republic in the "spring wheat – peas – winter rye" crop rotation (2022–2024). Autumn tillage variants were: moldboard ploughing with PLN-3-35 plow to a depth of 20–22 cm (control); nonmoldboard tillage - stubble cultivation with KOS-3.0 to 14–16 cm, disking with BDM-4-3.2 unit to 12–14 cm; without autumn tillage. Pre-sowing cultivation for all experimental variants was carried out with a combined Pauk-6 implement to 6–8 cm. According to the values of the hydrothermal coefficient (HTC), the vegetation conditions in 2022 were optimal for crop cultivation (HTC = 1.0), and in 2023-2024 they were severely arid (HTC = 0.6). The greatest effect among the autumn tillage variants was obtained with nonmoldboard stubble cultivation: the soil density slightly differed from plowing, and the reserves of productive moisture in the 0-30 cm soil layer exceeded the control by 1.9–5.5 %; a higher soil pedality coefficient (3.3) was noted compared to the other experimental variants (3.0...2.7); the productivity of the crop rotation link (8.53 t/ha grain units) was obtained at the control level (8.83 t/ha grain units); the profitability of crop cultivation in the crop rotation link was 25.1 %, by 11.1 % above control. A variant of the experiment without autumn tillage (pre-sowing cultivation with a combined Pauk-6 unit), despite a significant decrease in the productivity of the crop rotation link (6.94 t/ha of grain units), stood out in terms of profitability of production (59.4 %) due to a significant reduction in direct costs. In addition, the beneficial effect of minimal tillage on the soil structure (the portion of fractions <0.25 mm is 58 % lower than after plowing) and the preservation of productive moisture reserves was noted.